Representation of Chinese Cultural Identity in the Films Assalamualaikum Beijing and Kukejar Cinta ke Negeri Cina - Susanti, Elizabeth; Yonatia, Jessica (PANGGUNG, 2026)
In Indonesian films, representations of Chinese identity that integrate Chinese cultural elements and Islamic values remain relatively underexplored, making them significant to examine in a cross-cultural context. This study analyzes how Chinese identity is represented in the films Assalamualaikum Beijing and Kukejar Cinta ke Negeri Cina, and how these cultural elements are connected to Islamic values. The research employs visual semiotic analysis, which explores the signs, symbols, visual elements, identity representations, and narratives of multiculturalism that appear in both films. The results show that Chinese identity is positioned as a bridge of cultural harmony through depictions of tolerance, historical proximity, and the process of religious assimilation between China and Indonesia. The novelty of this study lies in revealing the integration of Chinese culture and Islamic values, which is rarely addressed in Indonesian films, particularly through visual representations that emphasize diversity and the historical and cultural connections between China and Indonesia.